The Impact of Patent Portfolio on Competitive Landscape of Digital Signage Apparatus - Hendrix, Tommy; Berliandaldo, Mahardhika; Apriliyadi, Eki Karsani; Tri Ajie, Firman (Jurnal Manajemen Teknologi, 2021)
Abstract. The digital signage market has been flourishing every year, and this situation opens up new commercialization opportunities for stakeholders related to the acceleration function. The modern world has allowed technological innovation to satisfy market demands, primarily based on portfolio of patent information. The digital signage apparatus became an economical solution for the costly technology in the digital era. The purpose of this paper was to find the impact of the competitive landscape on the digital signage apparatus towards e-commerce development based on a patent portfolio from the WIPO database. The research was performed based on the patent information using Innograph software and information related to digital signage apparatus resulting in a total of 146 registered patents and 40 patents matching the research subjects. The results revealed that the patent portfolio on the digital signage apparatus has high perceived usefulness, but only few industries used this as a reference in benchmarking their technological competitiveness. This paper is beneficial to the industry that seeks for the impact of the latest technological implementation amidst the competitive commercialization of the digital signage apparatus.Keywords: Competitive Landscape; Digital Signage Apparatus; Impact; Patent Portfolio.Abstrak. Pasar signage digital telah tumbuh pesat setiap tahun, dan situasi ini menjadi kesempatan bagi para pemangku kepentingan terkait dengan percepatan fungsi komersialisasi. Di era modern menjadi masalah umum yang memungkinkan peningkatan teknologi untuk memasuki kebutuhan pasar, terutama dari portofolio melalui informasi paten. Peralatan signage digital menjadi solusi ekonomis dalam nilai mengenai di era digital sangat mahal. Tujuan dari makalah ini dilakukan untuk menemukan dampak lanskap kompetitif pada peralatan signage digital terhadap pengembangan e-commerce dengan portofolio paten dari database WIPO. Metode yang dilakukan melalui informasi paten menggunakan software Innograph dan informasi terkait penggunaan alat signage digital dengan hasil total 146 paten terdaftar dan cocok dengan subjek 40 paten. Hasil penelitian menunjukkan bahwa portofolio paten pada alat signage digital memiliki kegunaan yang dirasakan tinggi, tetapi lebih sedikit industri yang menggunakan ini sebagai referensi dalam tolok ukur daya saing teknologi. Makalah ini bermanfaat bagi industri yang ingin mengetahui dampak penerapan teknologi terkini dalam tingkat persaingan dalam komersialisasi peralatan signage digital.Kata kunci: Dampak; Lanskap Kompetitif; Portofolio Paten; Peralatan Digital Signage.